Explicit Computation of Robin Parameters in Optimized Schwarz Waveform Relaxation Methods for Schrödinger Equations Based on Pseudodifferential Operators (Communications in Computational Physics, 2020)
The Optimized Schwarz Waveform Relaxation algorithm, a domain decomposition method based on Robin transmission condition, is becoming a popular computational method for solving evolution partial differential equations in parallel. Alongwith well-posedness, it offers a good balance between convergence rate, efficient computational complexity and simplicity of the implementation. The fundamental question is the selection of the Robin parameter to optimize the convergence of the algorithm. In this paper, we propose an approach to explicitly estimate the Robin parameter which is based on the approximation of the transmission operators at the subdomain interfaces, for the linear/nonlinear Schrödinger equation. Some illustratingnumerical experiments are proposed for the one- and two-dimensional problems.
Keywords: Optimized Schwarz Waveform Relaxation; domain decomposition method; Schrödinger equation; dynamics; stationary states; Robin boundary condition; pseudodifferential operators; fast convergence.